Estimation of the parameter of the Pareto distribution manual Using the general mediator estimator - شاهين حمزة اسماعيل; حسن رعد فاضل (Journal of Economics and Administrative Sciences, 2009)
Estimation of the tail index parameter of a one - parameter Pareto model has wide important by the researchers because it has awide application in the econometrics science and reliability theorem. Here we introduce anew estimator of "generalized median" type and compare it with the methods of Moments and Maximum likelihood by using the criteria, mean square error. The estimator of generalized median type performing best over all.